Kompetensi, Disiplin Kerja, dan Pengawasan Terhadap Kinerja Karyawan Bagian Gudang PT. JNE Pakjo Kota Palembang - Deri Putra Pratama; Mohammad Kurniawan DP; Shafiera Lazuarni (CV. Ulil Albab Corp, 2024)
Performance is the outcome achieved by an organization, whether it is profit-oriented or non-profit-oriented, generated during a specific period of time. Performance reflects the level of achievement of implementing an activity/program/policy in achieving the goals, missions, and visions of an organization as outlined in the strategic planning of an organization. Performance is the result or representation obtained by an individual or organization for the tasks or work performed. This study aims to examine the influence of competence, work discipline, and supervision as independent variables on employee performance as the dependent variable. This research is quantitative, with data sourced from questionnaire distribution. A total of 60 respondent answers were successfully collected from warehouse employees of PT JNE Pakjo in Palembang City using the Slovin formula. The analysis results show that partially, with the significance value, competence (2.777), work discipline variable (2.224), and supervision (4.005) have a positive and significant influence on the variable of employee performance in accounting information (prob < alpha = 0.05). Simultaneously, the independent variables collectively have a positive effect on improving accounting information system performance (prob < alpha = 0.05).